Bouveret’s Syndrome: A Case-Based Review, Clinical Presentation, Diagnostics and Treatment Approaches - Ferhatoğlu, Murat Ferhat (Sisli Etfal Hastan Tip Bul, 2020)
Gastric outlet obstruction that arises from gallstones impacted in the distal stomach or proximal duodenum after passing through a cholecystoduodenal, cholecystogastric or rarely choledocoduodenal fistula is called as Bouveret’s syndrome and it accounts for approximately 1-3% of all the patients with gallstone ileus. Although treatment modalities, including stone removal or fragmentation with classical endoscopic devices, such as snares, and forceps or fragmentation of gallstones with new devices, such as electrohydraulic lithotripsy, laser, extracorporeal shockwave lithotripsy have been described. However, only 29% of the patients benefit from nonsurgical methods. Removal of the stone through a gastrotomy or enterotomy and performing cholecystectomy and fistula repair with a second operation is an approach recommended for older patients with comorbid diseases. In this paper, a case of Bouveret’s syndrome was presented. The authors also aimed to review the diagnosis, management and treatment of this rare disease and to update the previous reviews.